(untitled) (Indian Journal of Child Health, 2015)
Poisoning is a diagnosis seldom made in neonatal intensive care units as most clinical features such as lethargy, respiratory distress,and poor feeding mimic common neonatal conditions. An 8-day-old male baby presented with complaints of inconsolable crying, poorfeeding, and seizures for 1 day. On admission, he had bradycardia, copious secretions and pin-point pupils, which led to suspicion ofcholinergic over-activity. Cholinesterase levels were 2209 IU/L in baby which increased to 5936 IU/L on day 18 of life. There wasa history of charred vasambu (Acorus calamus) being applied over the tongue. Contamination of vasambu with organophosphateswas suspected which was confirmed by high performance thin layer chromatography analysis showing chlorpyrifos derivatives. Babyimproved gradually with supportive treatment and was discharged on day 18 of life.